Do mindfulness interventions improve road safety? A systematic review. (February 2019) - Koppel, Sjaan; Bugeja, Lyndal; Hua, Phuong; Osborne, Rachel; Stephens, Amanda N.; Young, Kristie L.; Chambers, Richard; Hassed, Craig
Highlights: A systematic review was conducted to examine the evidence regarding the relationship between mindfulness and road safety. 17 studies were identified that investigated the relationship between mindfulness or mind-wandering on road safety measures. The results of the review suggest that mindfulness may be particularly useful for preventing distracted driving. More research is warranted to specifically investigate the effectiveness of mindfulness as an intervention for reducing road trauma. Abstract: Mindfulness has been identified as a potentially effective intervention for reducing road trauma. In this paper, we report on the results of a systematic review which examined the evidence regarding the relationship between mindfulness and road safety. The review was conducted following PRISMA guidelines (PROSPERO 2017: CRD42017075704). The primary outcomes measured were crash or near-crash rates and the secondary outcomes were driving violations (including speeding and texting while driving) and driving performance (i.e., errors in driving simulator, etc.). This review was registered with PROSPERO 2017: CRD42017075704. A systematic search of databases from the disciplines of public health, psychology and transport safety (Ovid Cochrane Library, Ovid PsycINFO, Ovid EMBASE, CINAHL PLUS, Ovid TRANSPORT and TRID: TRIS and ITRD database) was conducted on February 7 th 2018. Seventeen studies (12 cross-sectional and 5 case-control) published between 2011 and 2017 met the inclusion criteria. These all focused on the association between mindfulness or mind-wandering on road safety measures including driving performance (vehicle control, reaction time), compliance with speed zones and traffic signals, near-crash and crash rates, as well as propensity to engage in distracted driving behaviours. The results of the review suggest that mindfulness may be particularly useful for preventing distracted driving. However, a number of limitations in the existing research are noted. It is clear that more research is warranted to specifically investigate the effectiveness of mindfulness as an intervention for reducing road trauma.